Hegel's philosophy of right - Brooks, Thom. (Chicester : John Wiley & Sons, 2011)
Hegel's Philosophy of Right presents a collection of new essays by leading international philosophers and Hegel scholars that analyze and explore Hegel's key contributions in the areas of ethics, politics, and the law. The most comprehensive collection on Hegel's Philosophy of Right availableFeatures new essays by leading international Hegel interpreters divided in sections of ethics, politics, and lawPresents significant new research on Hegel's Philosophy of Right that will set a new standard for future work on the topic.
Front Matter -- Introduction / Thom Brooks -- Ethics. Consequentialism and Deontology in the / Dean Moyar -- The Empty Formalism Objection Revisited / Fabian Freyenhagen -- On Hegel's Critique of Kant's Ethics / Robert Stern -- Politics. Hegel and the Unified Theory of Punishment / Thom Brooks -- Hard Work / Kimberly Hutchings -- Politics. Gender, the Family, and the Organic State in Hegel's Political Thought / Alison Stone -- Law. Natural Law Internalism / Thom Brooks -- Hegel on the Relation between Law and Justice / Alan Brudner -- Index.
Print version record.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Law -- Philosophy; Natural law; Ethics; Hegel, Georg Wilhelm Friedrich, 1770-1831.; Hegel, Georg Wilhelm Friedrich, 1770-1831. Grundlinien der Philosophie des Rechts; Political science; State, The; Law; LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; Law (Philosophical concept); Natural law; Electronic books